STRUKTUR KOMUNITAS BERUDU ANURA DI SUNGAI CIBEUREUM TAMAN NASIONAL GUNUNG GEDE PANGRANGO, JAWA BARAT - Welni Dwista Ningsih; Mirza D. Kusrini; Agus Priyono Kartono (Media Konservasi, 2013)
The use of various types of habitats can affect the structure of tadpole communities. The purpose of this study was to identify and measure: a) composition and diversity of Anuran species on two different seasons, b) distribution of tadpoles in different microhabitat types, and c) developmental  stages of tadpole in two different season. Quantitative sampling of amphibian larvae was carried out on along the 224 m transect in Cibeureum stream, Mount Gede-Pangrango National Park, West Java. Four species were found in Cibeureum stream were Leptophryne cruentata (37.10%), Megophrys montana (34.33%), Rhacophorus margaritifer (28.49%), and Huia masonii (0.07%). Cibeureum stream microhabitat can be grouped into torrents, riffles and shingle areas. Tadpoles were only found in riffles and shingle areas. Omitting H. masonii data from linear regression test showed that microhabitat variables did not significantly affect the presence of tadpoles. Most tadpoles were found in stage 25. The dominant stage of tadpole found were in Gosner growth stage 24-28 (no foot) for both dry and wet season, which indicated that the frogs in the Cibeureum stream reproduce throughout the year.  Key words: tadpoles, Anura, Cibeureum, Gunung Gede Pangrango National Park, community structure